Implementasi Home Visit: Tantangan dan Peluang bagi Guru BK dalam Menangani Kasus Siswa Berisiko Putus Sekolah di SMPN 23 Medan - Poetriku Pradhana; Dewi Febriana Purba; Pranika Pranika; Rezky Maiya; Chandra Wahyudi; Aida Fitriany (CV. ITTC INDONESIA, 2025)
The purpose of this study is to outline how Guidance and Counseling (BK) instructors at SMP Negeri 23 Medan use the home visit program to assist students who are at danger of dropping out of school, as well as to pinpoint the opportunities and difficulties that come up throughout this process. In-depth interviews, participant observations, and documentation studies of BK instructors, students, and parents were used to gather data for this qualitative case study study. The results of the study indicate that the home visit program has a positive impact on understanding students' conditions as a whole, strengthening the relationship between school and family, and encouraging improvements in student behavior and attendance. However, a number of challenges were found, such as limited time for BK teachers, lack of facility support, resistance from parents, and difficult location access. On the other hand, this program opens up strategic opportunities to build a more empathetic, in-depth, and student-based intervention approach. This study recommends that home visits be made a systematic program that is fully supported by school policies.